A review: Fundamentals of computational fluid dynamics (CFD) - Zawawi M.H.; Saleha A.; Salwa A.; Hassan N.H.; Zahari N.M.; Ramli M.Z.; Muda Z.C. (American Institute of Physics Inc., 2023)
Computational fluid dynamics (CFD) provides numerical approximation to the equations that govern fluid motion. Application of the CFD to analyze a fluid problem requires the following steps. First, the mathematical equations describing the fluid flow are written. These are usually a set of partial differential equations. These equations are then discretized to produce a numerical analogue of the equations. The domain is then divided into small grids or elements. Finally, the initial conditions and the boundary conditions of the specific problem are used to solve these equations. All CFD codes contain three main elements: (1) A pre-processor, which is used to input the problem geometry, generate the grid, and define the flow parameter and the boundary conditions to the code. (2) A flow solver, which is used to solve the governing equations of the flow subject to the conditions provided. There are four different methods used as a flow solver: (i) finite difference method; (ii) finite element method, (iii) finite volume method. (3) A post-processor, which is used to massage the data and show the results in graphical and easy to read format. 2018 Author(s).